A Study of Verbal Reasoning and ESL Vocabulary Learning from a Psycholinguistic Perspective - LAMRI, Imane (Journal of Human Sciences, 2018)
The present study is mainly interested in finding out the impact of verbal reasoning abilities; more precisely that of lexical inference,in improving ESLvocabulary learning. A group of twenty (20)female learners (aged between 19 and 21 years old), of about 220 third year learners/ LMD systemat the English department/ the University of Frère Mentouri/ Constantine1, were used in the study. The participantswere tested forthe dependent variable that was rated from Cloze Procedure Format activitiesthat were administered during the year 2014-2015, by the end ofsomelectures on Psychopedagogy. Every class, the learners were assigned a text in the latter fieldand had to fill in the blanks using provided technical termslearnt in the same lecture. The collected data was analyzed, after that,and results show that lexical inference, as a cognitive skill, corresponds to ESL technicalvocabulary learning